Irmandades religiosas, devoção e ultramontanismo em Porto Alegre no bispado de Dom Sebastião Dias Laranjeiras (1861-1888) - Tavares, Mauro Dillmann (Universidade do Vale do Rio do Sinos, 2006)
The manifestations of devotion of three religious brotherhoods from Porto Alegre, the São Miguel e Almas, Nossa Senhora da Conceição and Nossa Senhora do Rosário which congregated, respectively, Caucasian, mulatto and black brothers during the bishopric of Dom Sebastião Dias Laranjeira (1861-1888) are the focus of this thesis. The ultramontane strictness typical of the Catholic Restoration in the second half of the 19th century determined the intervention in the brotherhoods and the ruling of the devotional practices and the services of the worshipers. The analysis of the documents of these three brotherhoods revealed that although they had been the target of the ultramontane ruling action of D. Sebastião, they managed to keep many of their traditional manifestations of religious sensibility, intensifying their presence in the porto-alegrense scenario and introducing solidarity practices in the contacts kept with other brotherhoods. The reconstitution of the oppositions and the associations between the bish
Keywords: bispado; festa religiosa; história; irmandade religiosa; Porto Alegre; restauração; igreja católica; Ciências Humanas